Cinética de crescimento de Salmonella Heidelberg planctônicas e sésseis - Santos, Suelen Priscila (2018)
Foodborne diseases are caused by bacteria, viruses, parasites, toxins, and others. Of these, salmonellosis stands out a serious foodborne illness caused by the bacterium Salmonella spp. Salmonella Heidelberg (SH) is one of the most widely distributed serovars in the world, associated with human diseases. The contamination of food by Salmonella occurs mainly by crosscontamination between surfaces and food, once, surfaces may have bacteria adhered in the form of biofilms. The capacity of biofilm formation is dependent on the surface used in the processing plants and stainless steel is the most used. To avoid and remove biofilms from the surfaces, producing safe food, it is essential to study the growth kinetics of the microorganism involving the observation of growth phases and the behavior of sessile and planktonic cells as a function of different temperatures. The objective of this work was to evaluate the growth kinetics of planktonic and sessile SH maintained at 9 ± 1 ° C and 36 ± 1 ° C, compared them with bacterial modeling in the Pathogen Modeling Program (PMP) and ComBase Predictor. For the study of the growth curve of planktonic SH, an inoculum of 10 3 CFU of SH culture, added to tubes, in triplicate, containing tryptone broth of glucose-free soybeans kept aerobically in B.O.D. were incubated for 0 min, 01 h, 02 h, 03 h, 04 h, 06 h, 08 h, 10 h, 12 h, 18 h, 24 h at a temperature of 9 ± 1 ° C and 36 ± 1 ° C , 36 h, 48 h, 72 h, 96 h and 120 h, 144 h, 168 h and 192 h. After the incubation times the bacterial cells were quantified by the (Drop plate) and the results were expressed in CFU.mL-1. In the study of the SH curve in the sessile phase, the test pieces used were stainless steel coupons undergoing cleaning and sterilization procedures. For the formation of biofilms, the coupons were cultured in tubes submitted to the same protocol as the planktonic cell study. However, after the incubation periods the coupons were removed from the culture media and immersed in 0.1% Peptone Water (PW) for 1 minute, introduced into tubes containing 0.1% Pw, subjected to the ultrasonic bath (frequency of 40 kHz and power of 81 W for 10 minutes) and quantified by the method (Drop plate). The results show that planktonic and sessile SH cells have the highest generation times and lower specific rates at the temperature of 9 ± 1 ° C. At temperatures of 9 ± 1 ° C and 36 ± 1 ° C, generation times were longer and speeds smaller for planktonic cells than sessile. In addition, the growth curve of sessile cells presents a higher lag and exponential phase when maintained at 9 ± 1 ° C, while the largest stationary phase is at 36 ± 1 ° C. For planktonic cells the largest lag phase is at 9 ± 1 ° C and the highest exponential phase at 36 ° C. Thus, it is concluded that the kinetics of SH growth is influenced by the temperature and the planktonic and sessile phases, presenting the phases of the growth curve and specific speeds of growth. In the comparison between the xiv planktonic Salmonella Heidelberg growth curve and the bacterial models, different growth parameters were observed at 10 ° C in PMP and ComBase, and at 36 ° C the PMP modeling showed values closer to those found in SH. Therefore, the importance of handling and preserving foods at low temperatures is reiterated in order to control microbial growth, guaranteeing food safety.